Financing Urban Water Services in Kenya : Utility Shadow Credit Ratings - Kimani, Angela; Advani, Rajesh; Sy, Jemima (World Bank, Washington, DC, 2014)
The Water Services Regulatory Board (WASREB), with support from the Water and Sanitation Program, is exploring the potential for urban water services providers (WSPs) to access medium-term finance from commercial lenders. The debt will be used to finance infrastructure investment to improve access to water services by Kenyans. This paper presents the results of a credit assessment and shadow rating exercise for 43 urban WSPs. The objective of the credit assessment is to provide borrowers and lenders with an overview of the creditworthiness of WSPs to support access to local currency finance from the domestic financial market. It gives an overview of the credit capacity of water utilities, provides utilities with a diagnostic to identify areas for improvement, and exposes financial institutions to potential lending opportunities in the water sector. Commercial finance in water is seen as a supplementary resource to public finance, which remains the predominant source of investment funds in the sector.